Pedersen’s law and the rise of distinctive tone in Baltic and Slavic - Kortlandt, Frederik (Baltistica, 2018)
According to Pedersen’s law, the accent was retracted in Lith. acc.sg. dùkterį ‘daughter’
Keywords: Balto-Slavic; historical accentology; Pedersen's Law